The Reflective Online Practitioner Survey: The value in harvesting both qualitative and quantitative data - McBeath, Alistair (European Journal for Qualitative Research in Psychotherapy, 2022)
Two research projects are reported which describe how carefully designed online surveys can generate considerable quantities of both quantitative and qualitative data. There is a central focus on the value of embracing mixed methods research and how this can be enabled through the development of a standardised approach to online surveying called the Reflective Online Practitioner Survey (ROPS). The development of the Reflective Online Practitioner Survey confirms the central notion of mixed methods research that qualitative and quantitative data when collected and integrated in combination can offer a deeper understanding of phenomena than either typeof data would offer alone.